Scientific School of the Department of Theory of Management: Founders, Followers, Disciples - T. B. Shramchenko (Управление)
The article presented a brief description of the most salient features of founders, followers, students of the scientific school of the Department of theory of management of the State University of Management, who worked there for fifty years. Today the staff of the department gratefully remembers the contributions of notable scholars and practitioners in the shaping and development of the country’s first scientific school of management theory.